Association of vitamin D receptor gene variants with polycystic ovary syndrome: a meta-analysis - Xiao-Yuan Shi; Ai-Ping Huang; Duo-Wen Xie; Xiao-Long Yu (BMC, 2019)
Abstract Background Polycystic ovary syndrome (PCOS) is a common endocrine disorder in reproductive-age women. Multiple susceptible gene as well as environmental factors and their interaction each other are contributed to the PCOS risk. Several case-control studies have researched the associations of the vitamin D receptor gene (VDR) polymorphisms with PCOS susceptibility, but the jury is still out. Here, we carried out a meta-analysis to clarify polymorphisms between ApaI (C/A) (rs7975232), BsmI (G/A) (rs1544410), FokI (C/T) (rs10735810), TaqI (T/C) (rs731236) and Tru9I (G/A) (rs757343) in the VDR gene and PCOS susceptibility based on relative lager sample size. Methods English database of PubMed and Embase, and Chinese database of Wanfang and China National Knowledge Infrastructure (CNKI) databases were retrivaled for the relationship between VDR gene variates and PCOS susceptibility published before 31th, May 2018. Crude odds ratios (ORs) and its 95% confidence intervals (95% CIs) in different comparisons were used to detected the strength of the association. All the statistical analyses of the present meta-analysis were performed by STATA version 12.0 software. Results Totally, 3587 (PCOS group 1922; control group 1665) participants from 13 studies were included which met our inclusion criteria. A statistically significant association between VDR ApaI (rs7975232) polymorphism and PCOS susceptibility (C vs. A: OR = 1.19, 95%CI = 1.06~1.34, P = 0.004) was found in the overall population. After stratified by ethnicity, we showed that there is a significant association between VDR ApaI (rs7975232) polymorphism and susceptibility to PCOS in the Asian (C vs. A: OR = 1.21, 95%CI = 1.04~1.42, P = 0.016) population, but this association was not found in the Caucasian population. Additionally, a significant relationship between VDR BsmI (rs1544410) variates with PCOS susceptibility in the Asian (G vs. A: OR = 1.27, 95%CI = 1.06~1.53, P = 0.011) population, but this association was not found in the Caucasian population. We didn't find any association between VDR FokI (rs2228570), VDR TaqI (rs731236), VDR Tru9I (rs757343) and PCOS susceptibility in the overall and the subgroup populations. Conclusions Our findings demonstrated that VDR ApaI (rs7975232) and VDR BsmI (rs1544410) polymorphisms are correlated with susceptibility to PCOS in the Asian population and VDR TaqI (rs731236), VDR FokI (rs2228570), VDR Tru9I (rs757343) did not reveal a relationship with the PCOS susceptibility.